Women's experiences with cervical cancer screening in a colposcopy referral clinic in Cape Town, South Africa: a qualitative analysis. Issue 2 (17th February 2017) - Momberg, Mariette; Botha, Matthys H; Van der Merwe, Frederick H; Moodley, Jennifer
Abstract : Objective: The aim of this study was to explore and understand women's experience with cervical cancer screening and with the referral pathways for abnormal Papanicolau (Pap) smears. Design and setting: Focus group discussions were conducted with first time colposcopy clinic attendees at a tertiary hospital colposcopy clinic in Cape Town, South Africa during November 2014. A thematic analysis was conducted to identify key themes. Initial coding categories were drawn from the interview guide. Participants: 27 women participated in 4 focus group discussions. Results: Participants mean age was 34 years, most did not complete secondary level education and were unemployed. Negative community opinions relating to Pap smears and colposcopy referral might deter women from seeking treatment. Having a gynaecological symptom was the most commonly cited reason for having a Pap smear. Fear of having a HIV test performed at the same time as Pap smear and low encouragement from peers, were factors identified as potential access barriers. Participants commented on insufficient or lack of information from primary providers on referral to the colposcopy clinic and concerns and apprehension during waiting periods between receiving results and the colposcopy appointment were discussed. Conclusions: There is a strong and urgent need to improve current knowledge about cervical cancer and Pap smears and the necessity and benefits of timely access to screening programmes, results and treatment. Strategies such as community health education programmes and mass media interventions could be employed to disseminate cervical cancer information and address negative community perceptions. Better training and support mechanisms to equip healthcare providers with the skills to convey cervical cancer information to women are needed. The use of short message service (SMS) to deliver Pap smear results and provide patients with more information should be considered to improve waiting times for results and alleviate apprehension during waiting periods.